Implementation of Maqāṣid Al-Syarī’ah Concept in Human Resource Management at Muhammadiyah Boarding School Ki Bagus Hadikusumo Jampang Bogor - Munir, Muhammad Misbakul; Masyitoh, Masyitoh; Suradika, Agus; Bahri, Saiful (Green Publisher Indonesia, 2023)
The research aims to analyze, describe and find the concept of human resource management of Islamic educational institutions from the perspective of maqāṣid al-syarī'ah. This research answers two main problems, namely the conception and implications of maqāṣid al-syarī'ah in human resource management. To find the results of the study, researchers use a type of qualitative research with a case study approach. The results of this study construct this resource management with maqāṣid al-syarī'ah which consists of five perspectives, namely: ḥifẓ al-dīn (optimization of religiosity), ḥifẓ al-nafs (optimization of psychic and physical), ḥifẓ al-aql (optimization of reason), ḥifẓ al-māl (optimization of wealth) and ḥifẓ al-'irdh (optimization of honor / self-esteem), from this perspective the theory of human resource management maqashidi is built with five main components, namely: Mutadayyin (religion), ḏaki (intelligent), munazzam (manejerial) matīn al-khuluq (morality) mutamayyiz (performance/achievement).